DIAGNOSIS AND TREATMENT OF HELICOBACTER PYLORI INFECTION: MAIN STATEMENTS OF THE MAASTRICHT V/FLORENCE CONSENSUS REPORT (2015) - I. V. Maev; D. N. Andreev; D. T. Dicheva; Yu. A. Kucheryavyy; A. V. Zaborovskiy; E. V. Partsvania-Vinogradova (SINAPS LLC, 2017)
The article  reflects  the  main  statements of the  Maastricht  V/Florence Consensus  Report  (2015), dedicated  to  the  diagnosis and  treatment of Helicobacter pylori infection and associated  with this pathogen  gastroduodenal diseases. The above statements of the  Consensus Report are illustrated as the original, and their own comments.